The role of light in the plants world - Gilewski, Marian (Photonics Letters of Poland, 2019)
This article describes the differences in how people and plants perceive light. This is important in some artificial light applications. In particular, it concerns the horticulture area, in which LED lighting is increasingly used. There is a misunderstanding of the specifics of the environment in this area. As a result, even experienced lighting professionals design greenhouse lamps in the same way as for people. This article describes the negative consequences of this approach. Full Text: PDF References A. R. Young, J. Claveau, and A.B. Rossi, Ultraviolet radiation and the skin: Photobiology and sunscreen photoprotection, Jurnal of the American Academy of Dermatology, vol. 76, p. 100-109, Mar. 2017. CrossRef S. Pashiardis, S.A. Kalogirou, and A. Pelengaris, Characteristics of Photosynthetic Active Radiation (PAR) Through Statistical Analysis at Larnaca, SM Journal of Biometrics & Biostatistics, p. 1-16, Jun. 2017. CrossRef W. Bommel, Interior Lighting: Visual Mechanism. Springer Nature Switzerland AG., p. 3-23, 2019. CrossRef L.T. Sharpe, A. Jagla, and W. Jägle, A luminous efficiency function, V*(λ), for daylight adaptation, Journal of Vision, vol. 5, no. 11, p. 948-968, Apr. 2012. CrossRef I. Fryc, and E. Czech, Application of optical fibers and CCD array for measurement of luminance distribution, Proceedings of SPIE, vol. 5064, p. 18-21, Apr. 2003. CrossRef I. Fryc, Design issue of novel type of an illuminance meter photometric head, Jurnal of Modern Optics, vol. 56, no. 33, p. 1504-1508, Jul. 2009. CrossRef I. Fryc, and P. Tabaka, The influence of different photometric observers on luxmeter accuracy for LEDs and FLs lamps measurements, Optica Applicata, vol. 49(2), p. 345-354, Jul. 2019. CrossRef M. Liu, Y. Yan, Q. Xue, and L. Gong, The research and analysis of factors affecting Critical Flicker Frequency, 6th Int. Conference on Applied Human Factors and Ergonomics, Las Vegas, 2015. CrossRef W. Wojtkowski, SEPIC converter for high power LED lighting, Przeglad Elektrotechniczny, vol. 86, no. 10, p. 260-263, 2010. DirectLink W. Wojtkowski, Step-up converters for power LED power supply, Przeglad Elektrotechniczny, vol. 87, no. 4, p. 71-72, 2011. DirectLink Y. Berkovich, and all, LED crop illumination inside space greenhouses, in Reach, vol. 6, Elsevier, p. 11-24, 2017. CrossRef C.M. Campillo, R. Fortes and M.H. Prieto, Solar Radiation Effect on Crop Production, Mar. 2012 CrossRef I. Ashdown, Photometry and Photosynthesis: From Photometry to PPFD., Nov. 2015 DirectLink K.J. McCree, The Action Spectrum, Abasorptance and Quantum Yield of Photosynthesis in Crop Plants, Agricultural Meteorology, vol. 9, 191-216, Oct. 1970. CrossRef OSRAM Opto Semiconductors, Horticulture Lighting with LEDs, Nov. 2016 CrossRef Standard DIN 5031-10 Optical radiation physics and illuminating engineering. CrossRef EconoLux Indastries Ltd., What Light do Plants Need, Hong Kong, 2016. CrossRef M.B. Ali, L. Khandaker, and S. Oba, Comparative study on functional components, antioxidant activity and color parameters of selected leafy vegetables as affected by photoperiods, J Food Agric Environ, vol. 7, p. 392-398, 2009. CrossRef A. Szmidt-Jaworska, K. Jaworski, A. Tretyn, and J. Kopcewicz, The involvement of cyclic GMP in the photoperiodic flower induction of Pharbitis nil, Jurnal of Plant Physiology, vol. 161, p. 277-284, 2004. CrossRef A. Szmidt-Jaworska, K. Jaworski, and J. Kopcewicz, The Involvement of Cyclic ADPR in Photoperiodic Flower Induction of Pharbitis nil, Jurnal of Plant Growth Regulation, vol. 25, p. 233-244, Sep. 2006. CrossRef A. Szmidt-Jaworska, K. Jaworski, A. Zienkiewicz, M. Lenartowska, and J. Kopcewicz, Guanylyl cyclase activity during photoperiodic flower induction in Pharbitis nil, Jurnal of Plant Growth Regulation, vol. 57, p. 173-184, 2009. CrossRef Light Laboratory Inc., Goniophotometer Test Report HLG ELITE lamps. CrossRef U.J. Błaszczak, D.A. Aziz, L. Gryko, Influence of the spectral composition of LED lighting system on plants cultivation in a darkroom, Proceedings of SPIE, vol. 10445, p. 1-9, 2017. CrossRef